An intense, few-cycle source in the long-wave infrared - Wilson, Derrek J.; Summers, Adam M.; Zigo, Stefan; Davis, Brandin; Robatjazi, Seyyed-Javad; Powell, Jeffery A.; Rolles, Daniel; Rudenko, Artem; Trallero-Herrero, Carlos A. (My University, 2019)
For the last several decades, the wavelength range accessible for strong-field, few-cycle studies has remained limited to the visible, near infrared and mid-wave infrared regimes. In particular, sources in the long-wave infrared have been lacking. We report the development of a 1 kHz, few-cycle laser source with up to a 9 μm central wavelength and gigawatt peak powers. When focused, this source can ionize gas targets, which we demonstrate here through the ionization of atomic xenon at wavelengths ranging from 5 μm to 9 μm. This opens up new opportunities for fundamental atomic and molecular physics, enabling experimental tests of strong-field ionization theories in the extreme long-wavelength, few-cycle limit and the direct excitation of vibrational transitions in organic molecules.
Keywords: Atomic and molecular interactions with photons; Nonlinear optics; Ultrafast lasers; Ultrafast photonics